Hacktivism Sebagai Upaya Menyampaikan Suara Lewat Ruang Siber Di Indonesia - Persadha, Pratama (Universitas Merdeka Madiun, 2020)
Abstractâ€” Hacktivism is becoming a trend that is being loved globally. The hacktivism trend was born at the same time as the information technology revolution, especially when people became increasingly dependent on smartphones and the internet. This has more or less affected aspects of cybersecurity in various countries. Because generally hacktivism appears with socio-political motives. Many countries have made cybersecurity one thing to study before deciding to cooperate with other countries. Also for Indonesia, cybersecurity has become an important factor in seeing national security. Several popular issues have shown that hacktivism has become a trend in Indonesia as well.Â Keywordsâ€”: Hacktivism; Hacktivist; Cybersecurity; hackers; social politics.